Parental Alcohol Use and the Alcohol Misuse of their Offspring in a Finnish Birth Cohort: Investigation of Developmental Timing. - Parra, Gilbert R.; Patwardhan, Irina; Mason, W. Alex; Chmelka, Mary B.; Savolainen, Jukka; Miettunen, Jouko; Järvelin, Marjo-Riitta (Journal of Youth & Adolescence, 2020)
There is a positive association between parental alcohol use and the alcohol use of their offspring. It is less clear whether this relation exists at different developmental periods. The purpose of the current study was to examine the associations between parental alcohol use at two developmental periods (prenatal and adolescence) and the alcohol misuse of their offspring at two developmental periods (adolescence and young adulthood). Data from the Northern Finland Birth Cohort 1986 (NFBC1986; n = 6963; 51% of offspring were girls) were used. The NFBC1986 is a population-based study of individuals born during a 1-year period in Finland. Multi-informant (parent, teacher, and youth) and multi-method (surveys and population registers) data were collected at four developmental periods (prenatal, childhood, adolescence, and young adulthood). The findings indicated that parents' alcohol use was stable from the prenatal period to adolescence. Mothers' and fathers' (based on mothers' perceptions) alcohol use during the prenatal period and adolescence were directly related to adolescents' heavy drinking. Prenatal alcohol use by mothers and fathers were related to young adults' alcohol use disorder indirectly (but not directly) through mothers' and fathers' alcohol use during adolescence and then through adolescents' heavy drinking. The results suggest that early and ongoing screening for alcohol use by mothers and fathers could help identify individuals at risk for heavy drinking and alcohol-related problems during adolescence and young adulthood.